(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to explore the contribution of Islamic Education (PAI) teachers in the learning evaluation process, from the planning and implementation stages to the processing of results and follow-up. A qualitative method was used through a literature review, in which data were obtained by searching and analyzing various sources, including books, scientific journal articles, and previous studies related to PAI learning evaluation. Data collection was carried out through documentation, while the analysis applied a content analysis model with steps of data simplification, data presentation, and conclusion drawing. The findings show that PAI teachers play a crucial role in developing evaluation objectives and tools that cover cognitive, affective, and psychomotor aspects, implementing formative and summative evaluations in a balanced manner, and processing evaluation results to inform remediation and enrichment programs. The implications of this study emphasize the need to improve Islamic Education teachers’ abilities in learning evaluation so that the assessment process becomes objective, responsible, and focused on comprehensive character building for students